Psychology in Malaysia : current research and future directions - Noor, Noraini M. (Pearson, 2012)
This book is organised into three main parts; current empirical research, non-empirical papers and future directions. The first part consists of seven empirical papers that report on current psychological research, starting with those that represent new areas of research in psychology in Malaysia and those that consider aspects of indigenization. The second part of the book comprises of five non-empirical papers and the final part is dedicated to two papers examining challenges of the profession that psychologists need to confront to remain relevant and effective.